Training in the Gendered Labour Market: New Realities, Requirements, and Rewards for Canadian Women - Quinlan, Elizabeth (Atlantis)

(untitled) (Mount Saint Vincent University, 2006)
This study investigates the gender dimension of the dynamic relationship between training and other aspects of the reward structure of the labour market by using structural equation modelling to develop a causal model of women's training participation based on feminist theory. The model uses data from Statistics Canada's new Workplace and Employee Survey (WES).